The Complete Plays of Jean Racine : Volume 3: Iphigenia - Racine, Jean, 1639-1699 (Book collections on Project MUSE., 2010)
"An English translation, in iambic pentameter couplets, of The Fratricides, a play by seventeenth-century French playwright Jean Racine"--Provided by publisher